Efektivitas Program Pusat Informasi dan Konseling Remaja (PIK-R) Pada Kasus Pernikahan Dini di Kecamatan Taman Kabupaten Sidoarjo - Mochammad Alvin Avisena; Tukiman Tukiman (Policy, Law and Political Research Center, 2026)
Early marriage remains a social issue that affects the quality of human resources, particularly among adolescents. The government, through the National Population and Family Planning Board (BKKBN), implements the Youth Information and Counseling Center (PIK-R) Program to provide adolescents with access to information and counseling services and to prevent various youth-related problems, including early marriage. This study aims to examine the effectiveness of the PIK-R Program implementation in Kedungturi Village, Taman District, Sidoarjo Regency. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation over a two-month period. The informants consisted of the Head of the Family Planning and Family Resilience Division of DP3AKB Sidoarjo Regency, the Family Planning Field Officer (PLKB) of Taman District, the Kedungturi Village midwife, PIK-R administrators, and local adolescents. Program effectiveness was analyzed using five indicators proposed by Sutrisno: program understanding, target accuracy, timeliness, goal attainment, and tangible change. The findings indicate that the PIK-R Program has not been fully effective, primarily due to limited program dissemination, low adolescent participation, and budget constraints. Nevertheless, the program is implemented regularly on a monthly basis and remains flexible in accommodating adolescents’ schedules. Furthermore, active participants demonstrated positive changes in attitudes and behaviors, such as increased openness and communication with peers. Overall, the PIK-R Program contributes positively to youth development as part of early marriage prevention efforts.